Performance Evaluation of EWARS (Early Awareness and Response System) for Leptospirosis Cases in Kebumen District Health Office in 2023 - Tumiat; Mukhibin, Akhmad; Maula, Ahmad Watsiq (BKM Public Health and Community Medicine, 2024)
Purpose: To evaluate the performance of the early warning and response system (EWARS) in the Kebumen District Health Office in 2023 in general and specifically for early detection of leptospirosis cases. Method: This study was a descriptive evaluation study using secondary data from EWARS platform. The data was retrieved from the website web.skdr.surveilans.org. Results: The timeliness of EWARS reporting at community health centers and hospitals levels in 2023 were 95.42% and 96.23%, respectively. The completeness of EWARS reports at community health centers and hospitals levels in 2023 were 98.11%, respectively. A total of 314 alerts were reported by community health centers, while 413 alerts reported from hospitals during 2023. The most frequently reported alert from hospitals was leptospirosis. In the EWARS, 66 cases of leptospirosis were reported at week 11. Alerts from hospital reports from week 1 to week 11 have an increasing trend. An alert from the health center report appeared in the 9th week. The response that has been made is improving a health awareness on a leptospirosis around the affected community health centers and hospitals in the Kebumen area. In term of verification, 93.46% of the alerts reported by hospitals were verified within 24 hours. Conclusion: The timeliness and completeness of EWARS reporting in Kebumen District have surpassed the national targets of 80% and 90%, respectively. In the case of leptospirosis, community health centers need to increase early detection of symptoms and risk factors for leptospirosis.